Renewable energy technology acceptance in Peninsular Malaysia / Roozbeh Kardooni - Roozbeh , Kardooni (2016)
Despite the application of a variety of policies, renewable energy resources have not developed in Malaysia. This PhD project investigates the factors that influence renewable energy technology acceptance in Malaysia, and attempts to show the impact of cost and knowledge on the perceived ease of use and the perceived usefulness of renewable energy technology. In general the aim of this study is to evaluate the impact of public perceptions (perceives of usefulness and perceived ease of use) about green technology especially renewable energy on using this kind of technology and to evaluate the impact of perceived of usefulness and perceived ease of use on the renewable energy acceptance in Peninsular Malaysia. The target population consisted of all peninsular Malaysian citizen aged 20 years and over with higher education (Includes trade and technical skills institution, post-secondary and tertiary) which is contained 21.75% of total population in this area (4893086). This study finds that the great majority of Malaysians (69.75%) have concern about term climate change. Results of this study also show that the term climate change evokes different free associations among the Malaysian public. Analysing the data indicated that 81% of respondents believe that the main cause of climate change is a human activity and Among a list of four human activities 32 % of respondents think climate change are caused mostly by emissions from vehicle and motorcycle. On the other hand analysis and results of Structural Equation Modelling (SEM) show that cost of renewable energy has an indirect effect on attitudes towards using renewable energy through the associated impact on the perceived ease of use and the perceived usefulness. The results also indicated that public knowledge in Malaysia does not affect perceived ease of use, although the positive impact of knowledge on perceived usefulness is supported